An investigation on human dynamics in enclosed spaces. (April 2018) - Trovati, Marcello; Asimakopoulou, Eleana; Bessis, Nik
Abstract: In this article, we introduce a method for analysing specific dynamical properties associated with the movement of people on a two-dimensional (compact) space. We focus on a variety of features defined by the topology and dynamics of the system to investigate human dynamics in enclosed spaces. This can potentially have significant applications within systems defined by human behaviour, particularly relevant to disaster management, internet of things (IoT), and big data analytics.